Evaluation of bioequivalence of two tablet forms of lisinopril in healthy volunteers - S. A. Altynbekov; G. A. Dzholdygulov; V. N. Seryakov; Y. M. Budach; O. E. Kurilo; N. I. Kuznetsova (Фармакокинетика и Фармакодинамика)
Under cross, single, open, randomized trial with 1 week washout period, with two sequences of 18 volunteers studied bioequivalence coated tablets, two manufacturers of lisinopril (20 mg dose). The concentration of lisinopril in the plasma samples was determined using HPLC with fluorimetric detection within 72 hours for the investigated preparations the following pharmacokinetic parameters were calculated:AUC0-∞, Cmax, tmax, Cmax/AUC. 90% confidence interval relations AUC0-∞ compared drugs totaled 0.8520 — 1.2102 for Cmax — 0,9288 — 1,1451. In addition to the 90% confidence intervals, analysis of variance revealed no statistically significant differences between the studied drugs. Concluded bioequivalence compared drugs lisinopril.